Study of Klein Gordon Equation with Minimum Length Effect for Woods-Saxon Potetial using Nikiforov-Uvarov Functional Analysis - Windy Andaresta; A Suparmi; C Cari (Journal of Physics: Theories and Applications, 2021)
The equation of Klein-Gordon for Woods-Saxon potential was discussed in the minimal length effect. We have found the completion of this equation using an approximation by suggesting a new wave function. The Klein-Gordon equation in minimal length formalism for the Woods-Sadon potential is reduced to the form of the Schrodinger-like equation. Then the equation was accomplished by Nikiforov-Uvarov Functional Analysis (NUFA) with Pekeris approximation. This method is applied to gain the radial eigensolutions with chosen exponential-type potential models. The method of NUFA is more compatible by eliminating vanishing the strict mathematical manipulations found in other methods. The energy calculation results showed that angular momentum, radial quantum number, minimal length parameter, and atomic mass influenced it. The higher the radial quantum number and angular momentum, the lower the energg. In contrast to the the minimal length, the energy will increase in value when the minimal length parameter is enlarged. An increase in atomic mass also causes energy to increase as the radial quantum number and angular momentum are held constant.